2019
DOI: 10.1002/htj.21620
|View full text |Cite|
|
Sign up to set email alerts
|

Three‐dimensional computational comparison of mini‐pinned heat sinks using different nanofluids: Part two—energy and exergy characteristics

Abstract: The energy and exergy characteristics of 3D-pinned heat sink (HS) designs have been computationally compared as the second part of a three-part investigation. Different pin profiles, such as circular, square, triangular, strip and elliptic pins, and without pin HS are conducted with three different types of nanofluids-Al 2 O 3 -water, SiO 2 -water, and CuO-water for laminar forced convection. The concentrations of nanofluids vary from 0 to 5 vol% with different Reynolds numbers ranging between 100 and 1000. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…They flowed water in a microchannel created in silicon chips and the maximum value of a heat flux they were able to reach was 790w/cm 2 without any change in phase with a pressure drop of 1.94 bar. Amer et al [9] discovered that the number of Nusselt depends on the Reynolds number in laminar microchannels flow [10]. This was observed clearly from their simulation with the use of microchannels inside diameters ranging from 3 to 81μm.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…They flowed water in a microchannel created in silicon chips and the maximum value of a heat flux they were able to reach was 790w/cm 2 without any change in phase with a pressure drop of 1.94 bar. Amer et al [9] discovered that the number of Nusselt depends on the Reynolds number in laminar microchannels flow [10]. This was observed clearly from their simulation with the use of microchannels inside diameters ranging from 3 to 81μm.…”
Section: Introductionmentioning
confidence: 87%
“…Different positions are selected at a fixed temperature of heat sink T sf = 35°C. Figure (10) demonstrates the diversity of thermal resistance versus heat loads, For thermal input power larger than 40 W, the (R th ) of the flat mini heat pipe is almost the same for all the positions taking into account the uncertainties of the thermal resistance, but for heat load lower than 40W, the flat mini heat pipe is sensitive to any change in direction. In fact, the position of thermosyphon displays the lowest thermal resistance, while the position of anti-gravity displays the highest one.…”
Section: Dual Influences Of the Inclination Angle And Heat Fluxmentioning
confidence: 97%
“…Luz Black Chrome Selective coating was used in this study. Emissivity of the Selective coating (𝜀 3 ) is calculated based on the temperature of the coating layer with the equation below [25]: 𝜀 3 = 0.0005333 (𝑇 3 + 273.15) -0.0856 (16) The equation used for the conduction across the wall of the absorber is used for the conduction through the glass envelope. The thermal conductivity of the glass cover is assumed to be constant with a value of 1.04 𝑊 𝑚.𝐾 (Pyrex glass) [26].…”
Section: Numerical Modelmentioning
confidence: 99%
“…ρ, Cp, K and μ are the density, specific heat capacity, thermal conductivity and dynamic viscosity respectively. Table 3 lists CuO thermo physical properties [12,25].…”
Section: Thermo Physical Properties Of the Heat Transfer Fluidmentioning
confidence: 99%
“…In addition, perforating the fins provides an improvement in terms of heat transfer is nearly 20%-30%, a decrease in pressure drop is up to 25%, and a reduction in heat sink mass is over 6%. Al-Damook et al 8,9 concluded that the pins containing five holes containing Nu are 11% larger than the cases of solid pins. These benefits arise due to not only the increased surface area but also heat transfer enhancement near perforation through the formation of localized air jets.…”
Section: Introductionmentioning
confidence: 99%